Study on the influence of roof load combination on deformation control of shallow buried tunnel section - Zhang Lin (Electronic Journal of Structural Engineering, 2023)
The shallow buried section of a tunnel exit in Kangding transit section of Kangxin Expressway in Sichuan Province is affected by the combination of loads on the roof of the tunnel, resulting in deformation phenomenon, which affects the safety and stability of tunnel construction. Based on the theory of elastic-plastic mechanics, combined with finite element numerical simulation, the article analyzes the stress distribution characteristics, plastic zone development and deformation characteristics of the surrounding rock of this tunnel section under different load combinations, exposes the influence of load combinations on the deformation of the tunnel, and puts forward a solution for the deformation of the surrounding rock in the course of this tunnel construction. The results show that the stress at the foot of the tunnel is more concentrated in the early stage of tunnel excavation, and the stress at the foot of the tunnel produces a maximum value of stress, which gradually decreases from the foot of the arch to the top of the arch. The load combination has no significant effect on the stress concentration areas, but will significantly increase the stress values at the foot of the arch. After excavation, the plastic zone of peripheral rock appears at the location of the side wall. With the construction of the primary support, the primary support bears the lateral pressure of the peripheral rock and transmits the pressure of the peripheral rock to the foot of the tunnel primary support, and the plastic zone is then transferred to the peripheral rock at the bottom of the foot of the primary support. The greatest deformation of the tunnel surrounding rock occurs at the roof or bottom of the tunnel, and the amount of displacement increases continuously with the increase of load. For the deformation characteristics of the tunnel surrounding rock after tunnel excavation and after various types of loads are applied during the construction process, the deformation control measures to be taken under each working condition are proposed, and these measures have a positive effect on the stability of the tunnel structure.